ANALISIS INTERNALISASI NILAI-NILAI KARAKTER UNTUK ANAK USIA DINI - Sisca Maghfiroh Auliyah Sulhan; Nur Fatimah; Debby Adelita Febrianti P (Early Childhood Islamic Education, 2025)
This study aims to analyze the process of internalization of character values ​​in early childhood at RA Perwanida 1, Patokan Village, Kraksaan District. Internalization of character values ​​at an early age is very important as a basis for the formation of children's personality and morals. This study uses a qualitative approach with a case study method. Data collection techniques are carried out through direct observation of learning and habituation activities, in-depth interviews with teachers and parents, and documentation of learning documents. The results of the study indicate that the internalized character values ​​include religious values, discipline, honesty, responsibility, and cooperation. The internalization process is carried out through character-based thematic learning strategies, teacher role models, daily habits, and active cooperation between schools and parents. Although the process is generally effective, several obstacles are still found, such as the lack of consistent standards for character values ​​at home and differences in child development in absorbing these values. Therefore, teachers' active parental involvement and individual approaches are necessary solutions. This study emphasizes the importance of synergy between the school and family environments in forming strong and sustainable children's characters from an early age.